Murburn model of vision: Precepts and proof of concept. Issue 8 (6th June 2022) - Manoj, Kelath Murali; Tamagawa, Hirohisa; Bazhin, Nikolai; Jaeken, Laurent; Nirusimhan, Vijay; Faraci, Federico; Gideon, Daniel A.
Abstract: The classical paradigm of visual physiology comprises of the following features: (i) rod/cone cells located at the rear end of the retina serve as the primary transducers of incoming photo‐information, (ii) cis–trans retinal (C20 H28 O) transformations on rhodopsin act as the transduction switch to generate a transmittable signal, (iii) signal amplification occurs via GDP‐GTP exchange at transducin, and (iv) the amplified signal is relayed (as an action potential) as a flux‐based ripple of Na−K ions along the axons of neurons. Fundamental physical principles, chemical kinetics, and awareness of architecture of eye/retina prompt a questioning of these classical assumptions. In lieu, based on experimental and in silico findings, a simple space‐time resolved murburn model for the physiology of phototransduction in the retina is presented wherein molecular oxygen plays key roles. It is advocated that: (a) photo‐induced oxygen to superoxide conversion serves as the key step in signal transduction in the visual cycle, (b) all photoactive cells of the retina serve as photoreceptors and rods/cones serve as the ultimate electron source in the retina (deriving oxygen and nutrients from retinal pigmented epithelium), (c) signal amplification is through superoxide mediated phosphorylation of GDP bound to inactive transducin, thereby activating a GDP‐based cascade (a new mechanism for trimeric G‐proteins), and (d) signal relay is primarily an electron movement along the neuron, from dendritic source to synaptic sink. In particular, we specify the roles for the various modules of transducin and GDP‐based activation of phosphodiesterase‐6 in the physiology of visual transduction.